Offshoring Silicon Valley. - Greenhouse, Steven (American Prospect, 2008)
In an article adapted from his new book, The Big Squeeze: Tough Times for the American Worker, veteran New York Times labor writer Steven Greenhouse examines the movement of jobs in the high technology sector from the U.S. to lower-cost bases in such countries as India and China.